Pre-monsoon Season Food Plants and Feeding Preference of Blackbuck (Antilope cervicapra) in Krishnasaar Conservation Area of Nepal - Paudel, Roman; Yadav, Shailendra Kumar; Gautam, Apsara; Yadav, Soljar; Miya, Mahamad Sayab (FORESTRY: Journal of Institute of Forestry, Nepal, 2024)
The Blackbuck (Antilope cervicapra), one of the charismatic grassland animals, is native to the Indian subcontinent. In Nepal, it is confined to the protected areas of the western lowlands, namely the Krishnasaar Conservation Area and Shuklaphanta National Park. The pre-monsoon dietary preferences of blackbucks in enclosed habitats are not well understood. Hence, this study investigated the key grass species, blackbuck’s preferences over them, and behavior during feeding in the pre-monsoon season in the Krishnasaar Conservation Area. For this, vegetation data was collected with quadrat sampling (n = 45), and feeding preference was studied using a scan sampling method. A total of 21 species of grasses were recorded from the blackbuck’s habitat and grazing sites. Among them, Imperata cylindrica and Cynodon dactylon were the most dominant species. Cynodon dactylon and other species, such as Eleusine indica, Chyrsopogon aciculatus, Cyperus rotundus, and Hemarthria compressa, were most preferred by the blackbuck. There was no significant difference in the grazing and resting time (behavior) between males and females. Likewise, the behavior did not differ significantly between morning and evening. This study highlights blackbuck’s selective feeding and reliance on specific grass species, emphasizing the need for effective management of high-quality grassland habitats to support their population. The findings of this study could be valuable in removing unpreferred species and promoting selected preferred species to provide enough food for blackbucks in their habitats.